2016
DOI: 10.5137/1019-5149.jtn.19363-16.1
|View full text |Cite
|
Sign up to set email alerts
|

Compression rates and kyphosis angles after 1 year in the patients with ao type a thoracic, thoracolumbar, and lumbar fractures treated conservatively

Abstract: ABSTRACTinjury classification and severity score (TLICS), described by Vaccaro et al. (7). In this system, most type A fractures of the Arbeitsgemeinschaft für Osteosynthesefragen (AO) classification system, even burst-type fractures in the thoracolumbar junction that had usually been operated on before, are classified within the conservative treatment group █ INTRODUCTION T raumatic spinal fractures are quite common lesions. In recent years, there has been a trend towards conservative treatment instead of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…However, bone volume in normal populations varies widely by sex, age, and occupation, with potential implications for fracture prognosis. Studies have confirmed that OSTA is based on the data of the patient’s body weight and age, which can be easily obtained and can approximately reflect bone mass 9–11 . In this study, the original application of OSTA as a bone mass indicator to evaluate its effect on postoperative VHL.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…However, bone volume in normal populations varies widely by sex, age, and occupation, with potential implications for fracture prognosis. Studies have confirmed that OSTA is based on the data of the patient’s body weight and age, which can be easily obtained and can approximately reflect bone mass 9–11 . In this study, the original application of OSTA as a bone mass indicator to evaluate its effect on postoperative VHL.…”
Section: Discussionmentioning
confidence: 65%
“…At present, the worldwide research on the influencing factors of VHL after thoracolumbar fractures is limited to sex, age, bone mineral density, BMI, and so on. There are also studies on the influence of pedicle screw fixation on the loss of postoperative vertebral height in thoracolumbar fractures, such as the choice of operation, postoperative bed rest time, improper screw placement, and poor reduction 9,10 . However, none of these are the main influencing factors for postoperative vertebral body height loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2013, Vaccaro et al. incorporated a modified classification system called the AOSpine thoracolumbar spine injury classification system ( 7 ), which is a widely accepted and comprehensive classification system used for clinical practice and research ( 8 , 9 ). This classification system can guide treatment decisions and help with the formulation of surgical procedures ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%